2006
DOI: 10.1021/jf061451r
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Estimation of the Polyphenol Index in Wines Using a Laccase Biosensor

Abstract: The use of a laccase biosensor, under both batch and flow injection (FI) conditions, for a rapid and reliable amperometric estimation of the total content of polyphenolic compounds in wines is reported. The enzyme was immobilized by cross-linking with glutaraldehyde onto a glassy carbon electrode. Caffeic acid and gallic acid were selected as standard compounds to carry out such estimation. Experimental variables such as the enzyme loading, the applied potential, and the pH value were optimized, and different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 28 publications
3
55
1
4
Order By: Relevance
“…HRP was used as the recognition enzyme, at pH 6 -9 [12]. Tyrosinase, at pH 7.4 was used in [6] and laccase at pH 5.0 in [4]. Tyrosinase and buffer at pH 8.5 were used in [3] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HRP was used as the recognition enzyme, at pH 6 -9 [12]. Tyrosinase, at pH 7.4 was used in [6] and laccase at pH 5.0 in [4]. Tyrosinase and buffer at pH 8.5 were used in [3] .…”
Section: Resultsmentioning
confidence: 99%
“…Most laboratories determine the level of total phenol in wines by the FolinCiocalteu method, which is not an absolute measurement of the amount of phenolic materials but is based on their chemical reducing capacity relative to an equivalent reducing capacity of gallic acid in most situations [2]. However, caffeic acid is one of the phenols present in a high amount in wine and has been used as reference by some authors [3,4], when measuring the total content of polyphenols in wine. Caffeic acid has been studied by several groups [3][4][5][6][7], who found that it was the preferred substrate among other polyphenols analyzed, being redox recycled between the adsorbed laccase (enzymatic oxidation reaction) and the electrode (electrochemical reduction reaction).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzyme immobilisation is an integral part in the production of laccase-based biosensors constructed to measure concentrations of phenolic compounds in waste waters and other samples taken from the environment, to determine the phenol contents in wines, teas, and other beverages, to define concentrations of compounds in pharmaceutical formulations and medical samples, to screen plant extracts for phenolic compounds, and to detect toxic phenolic chemicals including xenobiotic compounds in various other materials (Ghindilis et al 1992, Yaropolov et al 1994, Leite et al 2003, Gomes et al 2004, JaroszWilkolazka et al 2004, Gamella et al 2006, Vianello et al 2006; see also Chapter 12 of this book). In addition, the involvement of molecular oxygen in laccase catalysis allows to measure oxygen with such biosensors, even at rather low levels (Gardiol et al 1996).…”
Section: Laccasesmentioning
confidence: 99%